Hakikat Manusia dan Pengembangannya melalui Pendidikan - St Wahidah Z (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Human is a questioning creature, where he has a desire to know everything. On the encouragement of this curiosity, humans will always want to find out about what they don't know. This research aims to prove that humans need education to develop their lives in order to satisfy their curiosity. Humans are the creation of God Almighty who has the highest degree among other creatures. The thing that distinguishes humans from other creatures is the mind, thoughts, feelings and beliefs to enhance the quality of life in the world. Education is very important for everyone. Where, Education aims to educate and develop the potential within. With the growth and development of each individual, creativity, broader knowledge, good personality, and being a responsible person will be formed. A child will not be able to make his choice in choosing his education if he is not guided from childhood to adolescence. Of course, as parents who already have knowledge of this matter, they should direct, guide and support children in their journey to achieve education. And back again, education is very important for humans so that their lives have direction.